Modular quantum gas platform - Hammel, Tobias; Kaiser, Maximilian; Dux, Daniel; Preiss, Philipp; Weidemüller, Matthias; Jochim, Selim (Physical review, 2025)
We report on the development of a modular platform for programmable quantum simulation with atomic quantum gases. The platform is centered around exchangeable optical modules with versatile functionalities. The performance of each module is disentangled from all others, enabling individual validation and maintenance of its outputs. The relative spatial positioning of the modules with respect to the position of the atomic sample is set by a global reference frame. In this way, the platform simplifies reconfiguration and upgrading of existing setups and accelerates the design of new machines in a time- and cost-efficient manner. Furthermore, it facilitates collaborations between different experimental groups. This standardized hardware design framework, which we call Heidelberg Quantum Architecture, paves the way towards a new generation of on-demand and highly adaptable quantum simulation experiments.
Veröffentlicht: 18 März 2025
Gesehen am 02.12.2025